Body fat composition determines outcomes before and after liver transplantation in patients with cirrhosis. Issue 8 (14th April 2022) - Engelmann, Cornelius; Aehling, Niklas F.; Schob, Stefan; Nonnenmacher, Ines; Handmann, Luise; Macnaughtan, Jane; Herber, Adam; Surov, Alexey; Kaiser, Thorsten; Denecke, Timm; Jalan, Rajiv; Seehofer, Daniel; et al.
Abstract: Cachexia occurs in late stages of liver cirrhosis, and a low‐fat mass is potentially associated with poor outcome. This study compared different computed tomography (CT)–derived fat parameters with respect to its prognostic impact on the development of complications and death before and after liver transplantation. Between 2001 and 2014, 612 patients with liver cirrhosis without hepatocellular carcinoma listed for liver transplantation met the inclusion criteria, including abdominal CT scan (±200 days to listing). A total of 109 patients without cirrhosis served as controls. The subcutaneous fat index (SCFI), the paraspinal muscle fat index, and the visceral fat index were assessed at L3/L4 level and normalized to the height (cm 2 /m 2 ). Data were collected and analyzed retrospectively. Low SCFI was associated with a higher rate of ascites and increased C‐reactive protein levels ( p < 0.001). In addition, multivariate Cox regression analysis adjusting for sex, age, body mass index (BMI), and Model for End‐Stage Liver Disease showed that decreasing SCFI was also associated with an increased risk of cirrhosis‐related complications ( p = 0.003) and death on the transplant wait list ( p = 0.013). Increased paraspinal and visceral fat were not only positively correlated with creatinine levels ( p < 0.001), BMI, and metabolic comorbidities (all p < 0.001) before transplantation, but also predictive for 1‐year mortality after transplantation. Conclusion: The distribution of body fat is a major determinant for complications and outcome in cirrhosis before and after liver transplantation. Abstract : The loss of subcutaneous fat index (SCFI) reliably predicted patients' survival and the occurrence of cirrhosis‐associated complications, such as infections and SBP. The visceral (VFI) and paraspinal muscle fat indeces (PSFI) showed no influence on survival or complications before transplantation. However, post‐transplant survival was affected by an increased VFI and PSFI.image